Water management in quinoa cultivation: quantification of the water footprint and climate projections in an inter-Andean valley - Flores Galindo, Fredy (2026)
Efficient water management in agriculture is key to the sustainability of crops in inter-Andean valleys (IAV), where water availability is at risk due to climate change (CC). Quinoa, as a strategic crop in these ecosystems, requires a detailed analysis of its water use to optimize its production without compromising water resources. This study quantified the water footprint (WF) (green, blue and grey) of three quinoa varieties (INIA 415 Pasankalla, INIA 420-Negra Collana and INIA 441-Señor del Huerto) harvested in a sandy loam soil in an IAV of Peru. In addition, the trend of the WF in 12 agricultural seasons was evaluated, and future climate scenarios (SSP1-2.6, SSP3-7.0 and SSP5-8.5) were projected to estimate the impact of CC on the crop's water demand towards 2090–2100. The results showed significant differences in water-use efficiency among varieties. INIA 441-Señor del Huerto showed the highest water efficiency, with a 3.20 t ha⁻¹ yield and a low total WF, making it more sustainable under CC conditions. In contrast, INIA 420-Negra Collana had a higher water demand, making it less viable under water-stress scenarios. Climate projections indicate an increase in water demand for quinoa under scenarios of greater radiative forcing, which underscores the need to develop water management strategies. These findings highlight the importance of selecting more efficient varieties for water use and adopting sustainable practices to mitigate the effects of climate change on quinoa production at IAV.